Macular translocation with 360° retinotomy for management of retinal pigment epithelial tear: long-term results. Issue 1 (24th June 2010) - Polito, A; Cereda, M; Romanelli, F; Pertile, G
Abstract : Background: To determine long-term functional and morphological changes after full macular translocation (FMT) with 360° retinotomy in patients with retinal pigment epithelium (RPE) tears, in light of the increasing number of reports of this complication following vascular endothelial growth factor (VEGF)-modulating therapy. Methods: We retrospectively reviewed a consecutive series of six patients with RPE tears secondary to neovascular age-related macular degeneration who underwent FMT with 360° retinotomy between March 2005 and June 2006. Preoperative and postoperative visual acuity, fundus fluorescein angiography (FA) and optical coherence tomography (OCT) were reviewed. RPE tears occurred spontaneously in three cases and after intravitreal triamcinolone in three cases. Preoperative and postoperative best-corrected visual acuity was converted to logarithm of the minimal angle of resolution visual acuity for analysis. Results: Mean postoperative follow-up was 39 months (range 36–50 months). At 12, 24 and 36 months mean visual acuity increased by 6.00 (5.3), 5.57 (5.54) and 6.67 (4.76) lines, respectively. This improvement was maintained at final examination. FA and OCT revealed pigment epithelium atrophy extending to the new fovea in one case only, which also had longer symptom duration. Conclusions: Long-term follow-up of FMT showed significant improvement in the majority of patients. FMT may be an option for cases of RPE tears of recent onset. Further investigations are necessary to determine FMT's role in tears developing during the course of anti-VEGF therapy.